Short-chain fatty acids inhibit bacterial plasmid transfer through conjugation in vitro and in ex vivo chicken tissue explants - Ott, Logan C.; Mellata, Melha (Frontiers in Microbiology, 2024)
The animal gut acts as a potent reservoir for spreading and maintaining conjugative plasmids that confer antimicrobial resistance (AMR), fitness, and virulence attributes. Interventions that inhibit the continued emergence and expansion of AMR and virulent strains in agricultural and clinical environments are greatly desired. This study aims to determine the presence and efficacy of short-chain fatty acids (SCFA) inhibitory effects on the conjugal transfer of AMR plasmids. In vitro broth conjugations were conducted between donor Escherichia coli strains carrying AMP plasmids and the plasmid-less Escherichia coli HS-4 recipient strain. Conjugations were supplemented with ddH2O or SCFAs at 1, 0.1, 0.01, or 0.001 molar final concentration. The addition of SCFAs completely inhibited plasmid transfer at 1 and 0.1 molar and significantly (P < 0.05) reduced transfer at 0.01 molar, regardless of SCFA tested. In explant models for the chicken ceca, either ddH2O or a final concentration of 0.025 M SCFAs were supplemented to the explants infected with donor and recipient E. coli. In every SCFA tested, significant decreases in transconjugant populations compared to ddH2Otreated control samples were observed with minimal effects on donor and recipient populations. Finally, significant reductions in transconjugants for plasmids of each incompatibility type (IncP1ε, IncFIIβ, and IncI1) tested were detected. This study demonstrates for the first time the broad inhibition ability of SCFAs on bacterial plasmid transfer and eliminates AMR with minimal effect on bacteria. Implementing interventions that increase the concentrations of SCFAs in the gut may be a viable method to reduce the risk, incidence, and rate of AMR emergence in agricultural and human environments.